Justice in the Internet Context: The Protection of Freedom of Expression Online Post Constitutional Court Decision Number 105/PUU-XXII/2024 - Syofyan Hadi (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2025)
The purpose of this study is to analyze justice on the Internet post Constitutional Court Decision Number 105/PUU-XII/2024 which provide strengthening of protection of freedom of expression on the Internet. This research is a normative legal research with a statutory, conceptual, and case approach. The results of the study found that restrictions on freedom of expression on the Internet in the Law on Electronic Information and Transaction are problematic because they are irrational, unfair, disproportionate, and tend to conflict with the 1945 Constitution of the Republic of Indonesia. Through Decision Number 105/PUU-XII/2024, the Constitutional Court has realized justice on the Internet by providing proportional protection of freedom of expression on the Internet. The decision provides freedom for everyone to express themselves on the Internet, such as conveying criticism, provided that their expression does not degrade the dignity or good name of others. Government institutions, professions, or positions are excluded from subjects that can be victims of defamation. The government can no longer prosecute citizens who criticize the policies it has taken. The decision provides guidelines for enforcing the law against violations of freedom of expression on the Internet.